Bidirectional Relationships Between Posttraumatic Stress Disorder and Social Functioning During Cognitive Processing Therapy. Issue 3 (May 2020) - Lord, Kayla A.; Suvak, Michael K.; Holmes, Samantha; Shields, Norman; Lane, Jeanine E.M.; Sijercic, Iris; Wagner, Anne C.; Stirman, Shannon Wiltsey; Monson, Candice M.
Abstract: This study investigated temporal relationships between posttraumatic stress symptoms and two indicators of social functioning during cognitive processing therapy. Participants were 176 patients (51.5% female, M age = 39.46 [ SD = 11.51], 89.1% White, 42.6% active duty military/veteran) who participated in at least two assessment time points during a trial of cognitive processing therapy. Posttraumatic stress disorder (PTSD) symptoms (PTSD Checklist for DSM-IV) and interpersonal relationship and social role functioning problems (Outcome Questionnaire–45) were assessed prior to each of 12 sessions. Multivariate multilevel lagged analyses indicated that interpersonal relationship problems predicted subsequent PTSD symptoms ( b = .22, SE = 0.09, cr = 2.53, p = .01, pr = .46) and vice versa ( b = .05, SE = 0.02, cr = 2.11, p = .04, pr = .16); and social role functioning problems predicted subsequent PTSD symptoms ( b = .21, SE = 0.10, cr = 2.18, p = .03, pr = .16) and vice versa ( b = .06, SE = 0.02, cr = 3.08, p < .001, pr = .23). Military status moderated the cross-lag from social role functioning problems to PTSD symptoms ( b = –.35, t = –2.00, p = .045, pr = .16). Results suggest a robust association between PTSD symptoms and social functioning during cognitive processing therapy with a reciprocal relationship between PTSD symptoms and social functioning over time. Additionally, higher social role functioning problems for patients with military status indicate smaller reductions in PTSD symptoms from session to session. Highlights: Social functioning is robustly related to PTSD symptoms throughout treatment Social functioning problem reduction predicts subsequent PTSD symptom reduction PTSD symptom reduction predicts subsequent social functioning problem reduction Social role functioning problems only predict PTSD symptoms for military status